2017
DOI: 10.1124/jpet.116.239137
|View full text |Cite
|
Sign up to set email alerts
|

Mogroside IIIE, a Novel Anti-Fibrotic Compound, Reduces Pulmonary Fibrosis through Toll-Like Receptor 4 Pathways

Abstract: Idiopathic pulmonary fibrosis is a progressive fibrotic lung disease, and eventually most patients develop respiratory failure with a median survival rate of 2 to 3 years after diagnosis due to the lack of clinically effective therapies. Mogroside IIIE (MGIIIE), a cucurbitane-type compound, was isolated from MGIIIE has shown the strongest inhibition of nitric oxide release, a crucial inflammatory factor, from lipopolysaccharide (LPS)-treated RAW264.7 cells compared with other mogrosides. In the pulmonary fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…In the present study, we found that mogroside V treatment was effective at reducing the OVA‐induced activation of NF‐κB in the lungs of mice. In other studies, it was reported that both mogroside IIIE and mogroside V attenuate lipopolysaccharide‐induced lung inflammation and acute lung damage by reducing the activation of NF‐κB signaling pathways (Shi et al, ; Tao, Cao, et al, ; Tao, Yang, et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we found that mogroside V treatment was effective at reducing the OVA‐induced activation of NF‐κB in the lungs of mice. In other studies, it was reported that both mogroside IIIE and mogroside V attenuate lipopolysaccharide‐induced lung inflammation and acute lung damage by reducing the activation of NF‐κB signaling pathways (Shi et al, ; Tao, Cao, et al, ; Tao, Yang, et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, many studies revealed that mogroside V has some health‐promoting effects including antioxidant (Chen, Wang, Qi, & Xie, ), anti‐inflammatory (Di, Huang, & Ho, ), and anti‐pancreatic‐cancer activities (Liu, Dai, Dou, Ma, & Sun, ). Mogroside V also protects mice from chemically induced damage to lungs (Shi, Zheng, Wang, Liu, & Chen, ; Tao, Cao, Xu, Xie, & Zhang, ; Tao, Yang, et al, ), attenuates high‐fat‐diet–induced obesity (Qi, Chen, Zhang, & Xie, ) and nonalcoholic fatty liver disease in mice (Zhang et al, ), and improves metabolism in mice with type 2 diabetes (Zhang et al, ). Nevertheless, the antiasthmatic effect of mogroside V has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%
“…34 Recently, emerging evidence showed that F I G U R E 6 The regulation role of miR-7 on Smad2 in LF. 35 39 TLR9 stimulation facilitated the proliferation and differentiation of cardiac fibroblasts through activating NF-κB pathway to protect hearts from cardiac rupture. B, Dual-luciferase reporter gene assay showed that miR-7 mimic reduced the luciferase activity of Smad2 3′UTR WT, and miR-7 inhibitor increased the luciferase activity of Smad2 3′UTR WT.…”
Section: Discussionmentioning
confidence: 99%
“…38 Mogroside IIIE protected against bleomycin-induced PF in vivo, and in vitro experiments further determined that MGIIIE suppressed fibroblast activation and collagen production through down-regulating TLR4/MyD88 MAPK signalling pathway. 39 TLR9 stimulation facilitated the proliferation and differentiation of cardiac fibroblasts through activating NF-κB pathway to protect hearts from cardiac rupture. 40 In this study, we Our data clearly determined that TLR9 agonist CpG-ODN remarkably up-regulated CCN2 and α-SMA expression levels, accelerated the collagen production and promoted the proliferation of LFs, resulting in the promotion of MF differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…MG-III reduced pulmonary fibrosis and may have therapeutic potential for treating fibrosis (Tao et al, 2017).…”
mentioning
confidence: 96%